The Symbolism of The Ruwat Banyu Panguripan Tradition: Culture and Religion Integration Perspective - Ilafi, Afiliasi; Sudardi, Bani; Subiyantoro, Slamet; Pitana, Titis Srimuda (IBDA` : Jurnal Kajian Islam dan Budaya, 2024)
This study aims to explore the symbols in the tradition of Ruwat Banyu Panguripan in the integration of culture and religion in commemorating the Islamic New Year in Pemalang Regency. Banyu panguripan literally means water of life. This tradition reflects a harmonious combination of cultural values and community beliefs correlated with the Islam adhered to. The Ruwat Banyu Panguripan ruwat tradition exists in the Pulosari District, especially at the Manunggal Jati Utama College. This study uses a qualitative approach with a qualitative descriptive method in collecting data through observation, interviews, and literature related to the tradition of Ruwat Banyu Panguripan. This research shows that the tradition of Ruwat Banyu Panguripan in Pulosari is not exclusively organized by the Wong Gunung Festival but also by the Manunggal Jati Utama College, which was formerly a member of the Prabasari Padepokan. The Ruwat Banyu Panguripan tradition aims to deliver each individual's wishes to God. In the process of Ruwat Banyu Panguripan, water intake comes from four directions of the compass (the west, west, south, and north). For several months, verses of the Qur'an were chanted by members of the College until, at the time of this unification, the Prophet's prayer was recited. It shows that preserving local culture is integrated with the routine of the Muslim community, specifically reading the Qur'an and praying to the Prophet in a clean and holy state.